Stable isotopes suggest the location of marine feeding grounds of South European Atlantic salmon in Greenland. (25th January 2020) - Almodóvar, Ana; Nicola, Graciela G; Ayllón, Daniel; Trueman, Clive N; Davidson, Ian; Kennedy, Richard; Elvira, Benigno
Abstract: Historical data on the oceanic distribution and migration routes of southernmost Atlantic salmon Salmo salar populations from Europe are almost non-existent, as no rigorous tagging initiatives have been conducted. Here, we used stable isotope data (δ 13 C and δ 15 N) of historic scale collections to identify the potential marine feeding areas of the largest salmon population in the Iberian Peninsula. Data were compared with published datasets from Northern Ireland, Wales, south England, and northeast UK coast, which correspond to series between 15- and 33-year long within the time period from 1958 to 2009. Temporal covariation in sea surface temperature, primary productivity, and δ 13 C values suggests that feeding areas of Iberian salmon are located around Greenland, both in the Labrador and the Irminger seas. Furthermore, δ 13 C values of Atlantic salmon from Canadian rivers reported in the literature are similar to those found in individuals from Spanish rivers. Our results suggest that Iberian salmon follow a westerly migration route towards Greenland instead of following the easterly branch of the North Atlantic current into the Norwegian Sea. Characterization of feeding patterns and migration routes might help to understand the causes of ongoing population decline and establish targeted conservation programmes for threatened Iberian salmon.